Perceptions of complementary/alternative medicine use and influence on evidence-based asthma medicine adherence in Malaysian children - Ramdzan, Siti Nurkamilla; Pinnock, Hilary; Liew, Su May; Sukri, Nursyuhada; Salim, Hani; Hanafi, Nik Sherina; Hussein, Norita; Suhaimi, Julia; Lee, Ping Yein; Cheong, Ai Theng; Ahad, Azainorsuzila Mohd; Cunningham, Steve; et al. (Nature Research, 2019)
Complementary and alternative medicine (CAM) is widely used especially in Asia including for childhood asthma. The use of CAM could influence adherence to evidence-based (E-B) medicine. We explored the views of carers of Malaysian children with asthma regarding the use of CAM for childhood asthma, and its relationship with self-reported adherence to E-B medicine. We used a screening questionnaire to identify children diagnosed with asthma from seven suburban primary schools in Malaysia. Informed consent was obtained prior to the interviews. We conducted the interviews using a semi-structured topic guide in participants’ preferred language (Malay, Mandarin, or Tamil). All interviews were audio-recorded, transcribed verbatim and coded using Nvivo. Analysis was performed thematically, informed by the Necessity-Concerns Framework. A total of 46 carers (16 Malays, 21 Indians, 9 Chinese) contributed to 12 focus groups and one individual interview. We categorised participants’ as ‘Non-CAM’; ‘CAM’; or ‘combination’ user. Cultural practices and beliefs in the efficacy of CAM resulted in widespread use of CAM. Most carers used CAM as ‘complementary’ to E-B medicine. Concerns about dependence on or side effects of E-B treatment influenced carers’ decisions to rely on CAM as an ‘alternative’, with an important minority of accounts describing potentially harmful CAM-use. Healthcare professionals should discuss beliefs about the necessity for and concerns about use of both E-B medicine and CAM, and provide balanced information about effectiveness and safety. The aim is to improve adherence to regular E-B preventer medication and prevent delays in seeking medical advice and harmful practices associated with CAM. © 2019, The Author(s).